Factors Affecting Adoption And Use Of Inttra In The Ghanaian Shipping Industry Using The Utaut Model - Tettey, T. (University of Ghana, 2017)
The purpose of this study was to explore the state of the art of existing shipping portals and other e-marketplaces in the shipping industry. The analysis was based on UTAUT model which was modified to suit the Ghanaian context in the study by exploring literatures on technology acceptance and adoption studies to have a broader perspective and adopt a literature survey approach to this study. The objectives of this study is therefore are to review literature regarding the usage of freight management systems; review theories and models used for studying Technology acceptance, use and adoption in general, identify factors that influence adopting INTTRA in the Ghanaian shipping industry. The study developed a modified model that explained the adoption and use of the INTTRA technology in the shipping industry in Ghana. This modified model can serve as a guide to strengthening the methods and factors that need improving in order to increase the use of INTTRA in Ghana. It will also provide a foundation for future research on technology adoption and use in other Sub-Saharan Countries.
Thesis (MA)
Keywords: Adoption; Inttra; Ghanaian Shipping Industry; Utaut Model; Ghana